Supportive Teacher Talk Features to Promote Students’ Responses ın EFL Classroom - Irmayani, Irmayani; Masruroh, Uzlifatul (Universitas Nahdatul Ulama Surabaya, 2023)
Teacher talk is as important in teaching English as a foreign language as it is in any other subject. Teacher talk is supposed to be the maximum exposure of target language in the classroom setting as a main pedagogic function employed as a medium of imparting metalanguage (Ellis, 2008). Through classroom observation with 32 students, this research investigates supportive teacher talk elements that inspire students to be responsive. They are 1) what kind of supportive teacher talk features to promote students’ responses in EFL Classroom; 2) what is the dominant type of supportive teacher talk features that promote students’ responses in EFL Classroom; and 3) how the students’ responses towards the supportive teacher talk features in EFL Classroom. The study's subject was an excellent English teacher who taught second-year students at a public senior high school in a range of English abilities. Field notes and recordings of classroom interactions on audio and video were used to gather the data. Findings revealed that in terms of classroom organization, the supportive teacher talk in EFL classrooms is in the form of the functions of classroom language, namely organization, interrogation, and interaction. The dominant form of supportive teacher talk that promotes students’ responses in an EFL classroom is interrogation. While the way the students responded to their teacher's talk mostly occurred when the teacher asked them questions.